Killers of the Flower Moon [large type] : the Osage murders and the birth of the FBI - Grann, David (Random House Large Print, 2017)
In the 1920s, the richest people per capita in the world were members of the Osage Indian nation in Oklahoma. After oil was discovered beneath their land, they rode in chauffeured automobiles, built mansions, and sent their children to study in Europe. Then, one by one, the Osage began to be killed off. The family of an Osage woman, Mollie Burkhart, became a prime target. Her relatives were shot and poisoned. And it was just the beginning, as more and more members of the tribe began to die under mysterious circumstances. In this last remnant of the Wild West -- where oilmen like J.P. Getty made their fortunes and where desperadoes like Al Spencer, the "Phantom Terror," roamed -- many of those who dared to investigate the killings were themselves murdered. As the death toll climbed to more than twenty-four, the FBI took up the case. It was one of the organization's first major homicide investigations and the bureau badly bungled the case. In desperation, the young director, J. Edgar Hoover, turned to a former Texas Ranger named Tom White to unravel the mystery. White put together an undercover team, including one of the only American Indian agents in the bureau. The agents infiltrated the region, struggling to adopt the latest techniques of detection. Together with the Osage they began to expose one of the most chilling conspiracies in American history.